Flexibly designable wettability gradient for passive control of fluid motion via physical surface modification - Keita Funayama; Atsushi Miura; Hiroya Tanaka (Scientific Reports, 2023)
Abstract Modified solid surfaces exhibit unique wetting behavior, such as hydrophobicity and hydrophilicity. Such behavior can passively control the fluid flow. In this study, we experimentally demonstrated a wettability-designable cell array consisting of unetched and physically etched surfaces by reactive ion etching on a silicon substrate. The etching process induced a significant surface roughness on the silicon surface. Thus, the unetched and etched surfaces have different wettabilities. By adjusting the ratio between the unetched and etched surface areas, we designed one- and two-dimensional wettability gradients for the fluid channel. Consequently, fine-tuned channels passively realized unidirectional and curved fluid motions. The design of a wettability gradient is crucial for practical and portable systems with integrated fluid channels.